2020
DOI: 10.1111/hsc.13037
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of transformational leadership for promoting professional social work competence with EBPA

Abstract: However, the mechanism by which these two levels of factors impact practitioners' attitudes towards EBP remains unclear. Evidence-based practice was introduced to the Chinese social work field very early (He, 2004). However, social work practice in China still lacks or has insufficient EBP (Bai, Wu, & Qi, 2017). EBP is important for health care social workers because of their high requirements to provide services in a professional and EBP-friendly environment. This study focuses on health care social workers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Leaders following TL are characterized by their ability to motivate employees to transcend self-interest and embrace elevated ideals, values and aspirations to achieve higher levels of performance (Hassan et al, 2018;Nasir et al, 2019). Zhang et al (2020) noted that past research has frequently shown a connection between TL and ECP. However, it is important to acknowledge that the relationship between TL and ECP is not consistently positive across all instances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaders following TL are characterized by their ability to motivate employees to transcend self-interest and embrace elevated ideals, values and aspirations to achieve higher levels of performance (Hassan et al, 2018;Nasir et al, 2019). Zhang et al (2020) noted that past research has frequently shown a connection between TL and ECP. However, it is important to acknowledge that the relationship between TL and ECP is not consistently positive across all instances.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, scholars have consistently delved into the determinants and influencers of ECP in the workplace (Yang et al , 2023; Kasımoğlu and Ammari, 2020). Academic studies on ECP show that one of the critical strategies for energizing and inspiring workers is leadership, particularly transformational leadership (TL) (Zhang et al , 2020; Mahmood et al , 2019). Leaders following TL are characterized by their ability to motivate employees to transcend self-interest and embrace elevated ideals, values and aspirations to achieve higher levels of performance (Hassan et al , 2018; Nasir et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The high rates of turnover in the social work field have severe implications for the quality, consistency, and stability of services provided to clients in need [5,6]. Meanwhile, in the context of China, as one of the means to innovate social governance, social work is playing an increasingly important role in assisting governments in service provision [7]. Accordingly, effectively retaining workers is a crucial task for both social work organizations and the government [8].…”
Section: Introductionmentioning
confidence: 99%
“…Organizational context plays an important role in facilitating organizational learning. The Organizational Learning in Hospitals Model (OL‐H) (Lyman et al, 2019) and subsequent research (Lyman et al, 2020; Lyman, Horton, & Oman, 2021) indicate six contextual factors are conducive to organizational learning: having a shared purpose and motivation (Zhang et al, 2020), psychologically safe relationships, crucial infrastructure, the skills necessary to engage in organizational learning (Mittal, 2019) and shared experience as a team (Table 1) (Lyman et al, 2019). According to the OL‐H, when these factors are present, efforts to engage in organizational learning (e.g.…”
Section: Introductionmentioning
confidence: 99%